A REVIEW ON PHARMACEUTICAL MINI TABLETS: NEW MODALITY TO ORAL DRUG DELIVERY - S, NAVEEN TAJ (Asian Journal of Pharmaceutical and Clinical Research, 2020)
The purpose of any selected drug delivery system (DDS) is to deliver drug to target site and to get the desired drug concentration for effective therapy. The main purpose of designing controlled or sustained DDS is to decrease the frequency of dosing and maximizing its efficiency by confining the area of action of the drug to a selected region. It is well-identified that solid oral dosage form, particularly tablets, is the most satisfactory form of delivering medication. In addition, some new variations are emerging such as mini tabs which offer more formulation flexibility. Oral controlled release DDS are classified into two categories like single unit dosage forms which include tablets, capsules, and multiple-unit dosage forms include pellets, granules, or mini tablets. Mini tablets are a new development in solid dosage forms and more beneficial and great substitute for granules and pellets. Mini tablets defined as tablets which are having diameter <3 mm and promising patient friendly drug delivery system and more acceptable in small children’s and old age people as they are easy to swallow and offer therapeutic benefits such as manufactured relatively easy, dose and formulation flexibility, combination release pattern, coating, and less solvent requirement. Dose dumping and local irritation can be avoided using mini tablets. This review highlights the various advantages of mini tablets, manufacturing processes, formulation possibilities, and their challenges.